Improving symptom management for people with amyotrophic lateral sclerosis. Issue 1 (1st July 2017) - Nicholson, Katharine; Murphy, Alyssa; McDonnell, Erin; Shapiro, Jordan; Simpson, Ericka; Glass, Jonathan; Mitsumoto, Hiroshi; Forshew, Dallas; Miller, Robert; Atassi, Nazem
ABSTRACT: Introduction: Symptomatic management is the main focus of ALS clinical care. We aim to report the prevalence of ALS‐related symptoms and characterize self‐reported symptomatic management. Methods: A symptom management survey developed by the Muscular Dystrophy Association Clinical Research Network was completed by ALS registrants. Logistic regression identified potential predictors of symptom prevalence, severity, and treatment. Results: A total of 567 ALS participants reported fatigue (90%), muscle stiffness (84%), and muscle cramps (74%) as most prevalent symptoms. Fatigue (18%), muscle stiffness (14%), and shortness of breath (12%) were most bothersome. Although fatigue was the most prevalent symptom, it was also least treated (10%). Neither location of care nor disease duration was associated with symptom prevalence, severity, or probability of receiving treatment. Discussion: This large patient‐reported symptom survey suggests that fatigue is the most prevalent, bothersome, and undertreated ALS symptom. Improving ALS symptom management is an unmet medical need and clinical trials of symptomatic treatments are needed. Muscle Nerve 57 : 20–24, 2018